Epiregulin confers EGFR-TKI resistance via EGFR/ErbB2 heterodimer in non-small cell lung cancer - Ma, Shiqi; Zhang, Lu; Ren, Yuan; Dai, Wei; Chen, Tingqing; Luo, Liping; Zeng, Juan; Mi, Kun; Lang, Jinyi; Cao, Bangrong (Oncogene, 2021)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are effective against non-small cell lung cancer (NSCLC) with EGFR -activating mutations. The mechanisms underlying EGFR-TKI resistance are not fully understood. This study aimed to analyze the effects of seven EGFR ligands on EGFR-TKI sensitivity in NSCLC cells and patients. Cells with EGFR E746-A750del mutation were treated with recombinant EGFR ligands, and analyzed for cell viability, proliferation, and apoptosis. shRNA knockdown of endogenous Epiregulin (EREG) or overexpression of exogenous EREG and immunofluorescence experiments were carried out. Public gene expression datasets were used for tumor microenvironment and clinical assessment. Among the EGFR ligands, EREG significantly diminished cellular sensitivity to TKIs and was associated with decreased response to erlotinib in NSCLC patients. EREG induced AKT phosphorylation and attenuated TKI-induced cellular apoptosis in an ErbB2-dependent manner. EREG induced the formation of the EGFR/ErbB2 heterodimer regardless of gefitinib treatment. However, overexpression or knockdown of EREG in cancer cells had little impact on TKI sensitivity. Single-cell RNA sequencing data revealed that EREG was predominantly expressed in macrophages in the tumor microenvironment. In addition, EREG-enriched macrophage conditional medium induced EGFR-TKI resistance. These findings shed new light on the mechanism underlying EGFR-TKI resistance, and suggest macrophage-produced intratumoral EREG as a novel regulator and biomarker for EGFR-TKI therapy in NSCLC.